Participatory Approach in Mapping and Stakeholder Involvement for Ciliwung River Sustainability - Rimun Wibowo; Gunawan Ismail; Budi Susetyo; Syarifah Sofiah Dwikorawati; Sukma Laksita Rahma; Hery Saputra; Sahul Sidik; Usep Saripudin (Universitas Ibn Khaldun Bogor, 2024)
The Ciliwung River, one of the large rivers in Indonesia, has experienced damage in the upstream area from waste pollution, landfills, and environmental damage. The Ciliwung watershed has experienced shallowing and is often affected by foam. There are many stakeholders who are concerned and have carried out many caring actions, including the Ciliwung Care Community (KPC) in Kedung Halang District, Bogor City. Therefore, this situation must be resolved properly, immediately, and sustainably. Stakeholders who have potential for the development and sustainability of the Ciliwung River are formulated through focus group discussions and divided based on stakeholder quadrants. Activities that can be carried out as a follow-up to stakeholder mapping and engagement are workshops inviting all stakeholders to present the existing conditions of each segment of the Ciliwung River so that sustainability activities can be formulated that can be implemented through support between stakeholders.